BUILDING MSMe RESILIENCE IN DIGITAL TRANSFORMATION: CASE STUDY AT PURBALINGGA BATIK CENTER - Asmi Ayuning Hidayah; Fitri Amalinda Harahap; Indrawan Firdauzi (SEAN Institute, 2023)
The contribution of MSMEs to economy sector, especially in developing countries, is very significant. In Indonesia, almost 90% of all business sectors. MSMEs have advantages over large companies because of their size and flexibility as well as agility and entrepreneurship. MSMEs have advantages compared to companies because of their size and flexibility as well as agility and entrepreneurship. However, MSMEs have the highest business risk of change, especially in the era of digitalization. Technological changes, millennial behavior and the pandemic that came at once meant that MSMEs were more severely impacted, suffered longer and recovered more slowly than larger businesses. One way for MSMEs to survive and be competitive is to have the ability to adapt to all rapid changes. This article examines the readiness and acceptance of digital technology among MSMEs in Purbalingga batik village in accepting change in the current era of triple disruption. The results of focus group discussions and in-depth interviews with MSME players in Purbalingga batik village show that difficulties and insecurity in using technology are the main obstacles that hinder business development.